2022
DOI: 10.1177/00034894221118769
|View full text |Cite
|
Sign up to set email alerts
|

What Prospective Applicants Look for on Otolaryngology Residency Websites

Abstract: Objective: To determine what prospective residency applicants look for on otolaryngology residency program websites. Study Design: Survey. Setting: The survey was distributed in a virtual format through Google Forms. A link to the survey was given at the University at Buffalo Otolaryngology Chautauqua, sent to Otolaryngology program directors with requests to forward to PGY1 residents and Otolaryngology interest groups, sent to medical school Otolaryngology interest group leaders, posted on Twitter through sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The criteria evaluated in this study were determined based on a survey study conducted by DiNardo et al that surveyed 101 fourth-year medical students applying to otolaryngology, re-applicants applying to otolaryngology, and current first-year otolaryngology residents [7]. A total of 38 criteria were listed and participants were asked to mark the components they hoped to see on otolaryngology residency websites.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The criteria evaluated in this study were determined based on a survey study conducted by DiNardo et al that surveyed 101 fourth-year medical students applying to otolaryngology, re-applicants applying to otolaryngology, and current first-year otolaryngology residents [7]. A total of 38 criteria were listed and participants were asked to mark the components they hoped to see on otolaryngology residency websites.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, they found that the top 10 components were sought by at least 80% of participants. These included the current resident list with photos, intern year schedule, call schedule/requirements, rotation schedule, comprehensive faculty list, benefits information, research requirements, salary information, research selection criteria, program contact email, and specific extra courses for residents [7]. Frequencies of each component in the present study are indicated by an asterisk in Table 2 [10,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Any information about a medical school that is easily accessible may influence selection committees. 4,5 Future research would be useful to ascertain how academic faculty perceive the US News & World Report medical school ranking lists and the implications of these perceptions.We hope that program directors and selection committees in Otolaryngology will consider their biases and think about what "holistic review" means when they make these important decisions about applicants.…”
mentioning
confidence: 99%
“…Any information about a medical school that is easily accessible may influence selection committees. 4,5 Future research would be useful to ascertain how academic faculty perceive the US News & World Report medical school ranking lists and the implications of these perceptions.…”
mentioning
confidence: 99%